Rpv Mediated Defense Responses in Grapevine Offspring Resistant to Plasmopara viticola - Tyrone Possamai; Daniele Migliaro; Massimo Gardiman; Riccardo Velasco; Barbara De Nardi (Plants, 2020)
Downy mildew, caused by the biotrophic oomycete Plasmopara viticola, is one of the most serious grapevine diseases. The development of new varieties, showing partial resistance to downy mildew, through traditional breeding provides a sustainable and effective solution for disease management. Marker-assisted-selection (MAS) provide fast and cost-effective genotyping methods, but phenotyping remains necessary to characterize the host–pathogen interaction and assess the effective resistance level of new varieties as well as to validate MAS selection. In this study, the Rpv mediated defense responses were investigated in 31 genotypes, encompassing susceptible and resistant varieties and 26 seedlings, following inoculation of leaf discs with P. viticola. The offspring differed in Rpv loci inherited (none, one or two): Rpv3-3 and Rpv10 from Solaris and Rpv3-1 and Rpv12 from Kozma 20-3. To improve the assessment of different resistance responses, pathogen reaction (sporulation) and host reaction (necrosis) were scored separately as independent features. They were differently expressed depending on Rpv locus: offspring carrying Rpv3-1 and Rpv12 loci showed the strongest resistance response (scarce sporulation and necrosis), those carrying Rpv3-3 locus showed the highest levels of necrosis while Rpv10 carrying genotypes showed intermediate levels of both sporulation and necrosis.